Sincere voting in large elections - Acharya, Avidit; Meirowitz, Adam (Games and economic behavior, 2017)
Austen-Smith and Banks (1996) showed that sincere/informative voting is not typically an equilibrium of the Condorcet voting model when the size of the electorate is large. Here, we reverse their finding by adding a third type of voter—one that receives no information in favor of either of the alternatives—as well as global uncertainty about the probability that each voter is such a “no evidence type.” The expected number of no evidence type voters can be arbitrarily small; nevertheless, if the electorate is large enough, then each of the two standard Condorcet types votes sincerely in every nondegenerate type-symmetric equilibrium.